PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT SORAYA BEDSHEET PEKANBARU - Anuar, Saiful (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted at the PT. Soraya Bedsheet Pekanbaru. The purpose of this study was to determine the effect of work discipline on the performance of employees in the production department at PT Soraya Bedsheet Pekanbaru. The population in this study were 31 people. In this study, the sampling used saturated samples, namely 31 people. The data analysis used is simple linear regression. The results of this study indicate that the work environment has a significant effect on the performance of employees in the production department at PT Soraya Bedsheet Pekanbaru. The magnitude of the influence of work discipline on employee performance is 34.5%, while the remaining 65.5% is influenced by other variables not examined in this study